Funktion und Organisation germanistischer Fachzeitschriften in der zweiten Hälfte des 19. Jahrhunderts. Eine Analyse am Beispiel der Germania. Vierteljahrsschrift für deutsche Alterthumskunde (1856–1868) und der Beiträge zur Geschichte der deutschen Sprache und Literatur (1874–1891) - Zawrel, Sandra (2015)
The emergence of journals and the differentiation of academic publishing houses were closely interconnected in the second half of the 19th century. So far, however, this interdependence has hardly been researched, for journals are almost exclusively perceived as the mirrors of intellectual history. The present study ties in with this desideratum. It examines the development of two German Studies journals in the context of interdependence between academia and academic publishing houses as well as in the context of endogenous and exogenous determining factors. This involves the consideration of functional and organizational aspects. The following questions guide the analysis: What functions did the journals have for academic communication and what was their significance for the publishing houses in terms of program strategies? Which contributions did the editors and publishers make for successful publication? The study is based on sources. On the one hand, it draws on selected journal volumes; on the other hand, it uses a compiled corpus of sources consisting of correspondence between the respective editors and publishers. It becomes clear that in both journals, conveying and discussing knowledge were the dominant functions for academic communication. Furthermore, successful publication depended on the motivation and economic stability of the publishing houses. Integrating the journal into an overall programme objective formed the basis for a permanent existence. Through the journals, publishing houses forged links to the academic community which in turn proved to be economically useful to them.
BUCHWISS::pub-433